2023
DOI: 10.1177/17588359231212184
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory indices as prognostic markers in metastatic colorectal cancer patients treated with chemotherapy plus Bevacizumab

Alessandro Passardi,
Irene Azzali,
Alessandro Bittoni
et al.

Abstract: Background: Validated predictors of sensitivity or resistance to Bevacizumab (Bev) are not available, and Inflammatory Indexes (IIs) has been reported to be useful prognostic factors in various malignant solid tumours, including metastatic colorectal cancer (mCRC). Objectives: To explore the prognostic value of IIs in mCRC patients treated with first-line chemotherapy plus Bev. Design: One hundred and eighty-two patients diagnosed with mCRC and treated with first line chemotherapy plus Bev were considered for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…The Warburg effect refers to the ability of cancer cells to derive energy through glycolysis even under aerobic conditions. Therefore, elevated serum LDH levels may reflect increased cancer cell activation and are associated with poor prognosis in cancer patients [34]. The results of our study are compatible with those of previous studies [19,23,24,[32][33][34][35], and LDH was identified as a factor associated with unfavorable outcomes in extensive-stage SCLC patients who received first-line anti-PD-L1 ICIs combined with chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The Warburg effect refers to the ability of cancer cells to derive energy through glycolysis even under aerobic conditions. Therefore, elevated serum LDH levels may reflect increased cancer cell activation and are associated with poor prognosis in cancer patients [34]. The results of our study are compatible with those of previous studies [19,23,24,[32][33][34][35], and LDH was identified as a factor associated with unfavorable outcomes in extensive-stage SCLC patients who received first-line anti-PD-L1 ICIs combined with chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, elevated serum LDH levels may reflect increased cancer cell activation and are associated with poor prognosis in cancer patients [34]. The results of our study are compatible with those of previous studies [19,23,24,[32][33][34][35], and LDH was identified as a factor associated with unfavorable outcomes in extensive-stage SCLC patients who received first-line anti-PD-L1 ICIs combined with chemotherapy. The three female patients in this study had significantly shorter OS than the male patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, research has shown that SII is associated with a heightened risk of mortality in adults with asthma 33 . Within oncology, studies established SII as an independent prognostic factor for overall mortality, underscoring its potential utility as a prognostic marker 34 , 35 . In cardiac surgery, a meta-analysis involving over 3245 patients revealed that a high preoperative SII significantly predicts an increased risk of postoperative atrial fibrillation, suggesting its value as a predictive biomarker 36 .…”
Section: Discussionmentioning
confidence: 99%
“…It is derived from a formula incorporating levels of specific immune system markers obtained from complete blood counts, specifically, (platelets × neutrophils) / lymphocytes 7 . Traditionally, SII has been utilized as a mortality predictor for patients with various tumors 6 , 7 , 34 , 36 , cerebrovascular diseases 8 , 9 , 11 , and cardiovascular conditions 9 , 10 , 12 . The scope of SII's application has been broadening, with recent research indicating its potential in forecasting disease severity and monitoring the efficacy of treatments 13 17 .…”
Section: Introductionmentioning
confidence: 99%